PENGARUH IKLIM ORGANISASI TERHADAP PRODUKTIVITAS PEGAWAI PADA BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN SUBANG - Anissa, Indah Firizqiani; Diah Andani, Diah Andani; Komara, A Moeslihat (The World of Public Administration Journal, 2023)
Abstract The purpose of this study was to find out how much influence organizational climate has on employee productivity at the Subang Regency Regional Revenue Agency (BAPENDA). This research method is a type of descriptive quantitative research. In its implementation using data collection techniques such as questionnaires, literature studies, and observations with a sample of 92 people to be used as respondents. The data analysis technique used is the t-test and the Product Moment Person formula with SPSS 24. Keywords:Ã‚Â  Organizational Climate and Employee Productivity